Libelocracy - Walker, Clive; Weaver, Russell L (Journal of Malaysian and Comparative Law, 2014)
â€œLibelocracyâ€ involves several elements. The first is the deployment of the law of libel by politicians against non-political publishers. Second, the use is tactical in a more directly political sense â€“ in other words, the action is brought against other politicians and is not for the vindication of purely private reputations. Third, the tactic develops into either repeated claims or a single large claim, sufficient to cause significant political damage to a political opponent. Fourth, by combining or repeating these tactics, libelocracy can become a major determinant of political success and failure. The paper will explain how defamation and related litigation, both civil and criminal, has impacted upon recent political life in Malaysia and Singapore in comparison to the United Kingdom. Some corrections, designed to encourage the confinement of political disputes within political forums, are suggested for Malaysia and Singapore, based upon developments in English common law.